Experimental and Thermodynamical Modeling of Ore-Forming Processes in Magmatic and Hydrothermal Systems - Galina Palyanova (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This special issue book includes 10 original research papers that discuss and solve some problems of ore-forming processes in magmatic and hydrothermal systems. Some of these papers in the issue deal with experimental and thermodynamical modeling, while the others are devoted to analytical geochemistry, geochronology and genesis of some ore occurrences. I hope that these papers will be useful for scientists who work on the fundamental problems of ore-forming processes and the genesis of ore deposits, and will provide new ideas for future research.